Revaccination against hepatitis B in late teenagers who received vaccination during infancy: Yes or no? - Hong Zhao; Yi-Hua Zhou (Taylor & Francis Group, 2018)
The significance of vaccination against hepatitis B during infancy is recognized worldwide, however, whether booster or revaccination after a period of time following the primary vaccination is required remains controversial. Recently, cross-sectional epidemiological surveys found that HBsAg prevalence in subjects born after the implementation of mass vaccination was increased with age, which was attributed to waning of anti-HBs over time. However, comprehensive analysis of the closely related cross-sectional surveys showed that the age-specific increased HBsAg prevalence was more likely associated with the carry-over of the infection occurred in early life, likely due to imperfect coverage of hepatitis B vaccination at the beginning of its introduction. Latest studies showed that booster response could be observed in the majority of individuals vaccinated 30 years ago. Moreover, confirmed breakthrough HBV infection with severe consequences in successfully vaccinated individuals is extremely rare. Thus far no compelling evidence has been acquired to support booster vaccination in adolescence. The uncertainty regarding the duration of protection of hepatitis B vaccination, especially beyond 30 years after the primary vaccination, merits a systematically designed study to follow the same cohort of participants longitudinally, which differs from the cross-sectional studies reported previously, can hopefully offer more direct evidence to help us to determine whether revaccination of hepatitis B vaccine is necessary.